Scientific and methodological prerequisites of the economic transformation of the public-private partnership project format - Kolisnyk, H. (Ways to Improve Construction Efficiency, 2022)
In today's conditions of globalization and intensification of economic processes, the issue of effective management of infrastructure projects is gaining particular relevance. Public-private partnership (PPP) is one of the key mechanisms that allows attracting private investments for the implementation of socially significant projects. In this context, an important role is played by scientific and methodical approaches to the transformation of the format of such projects, which make it possible to increase their efficiency, reduce risks and ensure stable economic development. The economic transformation of the format of PPP projects involves the introduction of new management models and methods that take into account the specifics of the modern market and dynamic changes in the macroeconomic environment. It is based on the use of science-based approaches that allow to optimize the processes of planning, financing and implementation of projects, while ensuring the high quality of the provision of services and infrastructure facilities. The scientific and methodological prerequisites for the economic transformation of PPPs include the analysis of existing partnership models, the assessment of risks and opportunities, as well as the development of new strategies and tactics of interaction between public and private entities. They take into account international experience and the specifics of national economies, which allows to adapt successful practices to local conditions and ensure their effective implementation. This work is devoted to the research of the scientific and methodological foundations of the economic transformation of the format of PPP projects. It examines the main approaches to the management of PPP projects, analyzes current trends and problems of their implementation, and also offers recommendations for improving the efficiency of these projects in the context of economic transformation.